POLA PENYELUNDUPAN NARKOBA PADA TIGA UNIT PELAKSANA TEKNIS PEMASYARAKATAN DI LINGKUNGAN KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA DAERAH ISTIMEWA YOGYAKARTA - Iqbal Rasyid Dharmawan; Odi Jarodi (Jurnal Komunikasi Hukum, 2024)
Drug abuse in Indonesia is a serious problem with the number of users reaching 3.3 million people in the 2021-2023 period, which is influenced by a lack of self-control, environmental influences, and weak educational outreach. In Yogyakarta Province, around 40% of drug users are students, while overcapacity in prisons exacerbates the potential for drug smuggling, including in Yogyakarta Class IIA Narcotics Prisons where drug convicts dominate. Therefore, this research was conducted to determine the description of drug smuggling patterns in the Correctional UPT in the Yogyakarta Regional Office of the Ministry of Law and Human Rights. Qualitative methods were used in this research to be able to describe more broadly the smuggling patterns that occurred using a case study research design and data collection using interviews, observation and document study. From the research conducted, the smuggling pattern that occurs at the Correctional UPT in the Yogyakarta Regional Office of the Ministry of Law and Human Rights has a tendency to use types of drugs or what are usually called koplo pills with the smuggling pattern being through visits or depositing goods, and the formation of networks is usually done when getting to know new people in prison.